The Transformation of a Historic Tradition: From Khabar to Ta’rikh (American Journal of Islam and Society, 1988)
IntroductionSome idea of the past is present in every culture, and historicalconsciousness as an awareness of this past is a distinctive element in totalcultural expression. Hence, it would be a mistake to assume that there wasno historical consciousness among the Arabs predating Islam. However, itwas the religious, political and social transformation of the Arabs throughIslam that motivated an extensive interest in the past and its systematicrecording.Muslim historians developed the idea of the past they had inherited frompre-Islamic Arabia and expressed it in an extensive historical literature. Thestudy of the past in early Islamic history was motivated and determined bya number of factors. This article seeks to outline some of the importantdevelopments which led to a distinctive Islamic historiography. It seeks todo so by an examination of studies conducted on the early Islamic historicaltradition. In particular, three fundamental aspects of the different phases ofhistorical writings from pre-Islamic Arabia through the 2nd and 3rd centuriesof the Hijrah are investigated: the external form of historical recollection;its subject matter; and the meaning and significance of both the form andthe subject matter of historical recollection in the culture.1. Pre-Islamic ArabiaThe interest in the past among the pre-Islamic Arabs is best exemplifiedby the custom of evening tribal gatherings, called majalis, at which the special ...